Emergence of impurity-doped nanocrystal light-emitting diodes - Luo, Dongxiang (2021)
In recent years, impurity-doped nanocrystal light-emitting diodes (LEDs) have aroused both academic and industrial interest since they are highly promising to satisfy the increasing demand of display, lighting, and signaling technologies. Compared with undoped counterparts, impurity-doped nanocrystal LEDs have been demonstrated to possess many extraordinary characteristics including enhanced efficiency, increased luminance, reduced voltage, and prolonged stability. In this review, recent state-of-the-art concepts to achieve high-performance impurity-doped nanocrystal LEDs are summarized. Firstly, the fundamental concepts of impurity-doped nanocrystal LEDs are presented. Then, the strategies to enhance the performance of impurity-doped nanocrystal LEDs via both material design and device engineering are introduced. In particular, the emergence of three types of impurity-doped nanocrystal LEDs is comprehensively highlighted, namely impurity-doped colloidal quantum dot LEDs, impurity-doped perovskite LEDs, and impurity-doped colloidal quantum well LEDs. At last, the challenges and the opportunities to further improve the performance of impurity-doped nanocrystal LEDs are described.